Activity Test Of White Frangipani Plant Stem Extract (Pulmeria Rubra L) Against Gram Positive Bacteria Staphylococcus Aureus ATCC 25923 - Olandina Cipriana Gusmao Freitas Boavida (International Journal of Health Engineering and Technology, 2026)
This study aims to test the antibacterial potential of ethanol extract of white frangipani stems (Plumeria rubra L.) against Staphylococcus aureus ATCC 25923 as a Gram-negative bacterium.‑positive for causing skin infections. The study used a true experimental laboratory design with a quantitative approach. The population was white frangipani plants on Jl. Palem, Cemani, Grogol, Sukoharjo, with samples in the form of fresh stems. The extract was made by maceration with 96% ethanol using a rotary evaporator, then standardized and phytochemically screened for alkaloids, flavonoids, saponins, and tannins. Antibacterial activity was tested using the well diffusion and agar disc diffusion methods, and the inhibition zone data were analyzed descriptively (mean ± SD) based on the strength classification criteria of <5 mm, 5–10 mm, 10–20 mm, and >20 mm. The results showed that the white frangipani stem extract contained alkaloids, flavonoids, saponins, and tannins, and produced a strong inhibition zone (10–20 mm) at concentrations of 20%, 40%, and 60% against Staphylococcus aureus ATCC 25923, with the highest inhibition zone of the positive control. In conclusion, the ethanol extract of white frangipani stems has the potential as a natural antibacterial agent against Gram-negative bacteria.‑positive, although further studies regarding MIC/MBC and toxicity are needed.